Retinoic acid signaling in axonal regeneration - Puttagunta, Radhika; Di Giovanni, Simone (Frontiers in Molecular Neuroscience, 2012)
Following an acute central nervous system injury, axonal regeneration and functional recovery are extremely limited. This is due to an extrinsic inhibitory growth environment and the lack of intrinsic growth competence. Retinoic acid (RA) signaling, essential in developmental dorsoventral patterning and specification of spinal motor neurons, has been shown through its receptor, the transcription factor RA receptor β2 (RARß2), to induce axonal regeneration following spinal cord injury (SCI). Recently, it has been shown that in dorsal root ganglia neurons, cAMP levels were greatly increased by lentiviral RARβ2 expression and contributed to neurite outgrowth. Moreover, RARβ agonists, in cerebellar granule neurons and in the brain in vivo, induced phosphoinositide 3-kinase dependent phosphorylation of AKT that was involved in RARβ-dependent neurite outgrowth. More recently, RA-RARß pathways were shown to directly transcriptionally repress a member of the inhibitory Nogo receptor complex, Lingo-1, under an axonal growth inhibitory environment in vitro as well as following spinal injury in vivo. This perspective focuses on these newly discovered molecular mechanisms and future directions in the field.